1998
DOI: 10.2741/a247
|View full text |Cite
|
Sign up to set email alerts
|

Aminoalkylaziridines as substrates and inhibitors of lysyl oxidase specific inactivation of the enzyme by n- 5-aminopentyl aziridine

Abstract: Introduction 3. Materials and Methods 3.1. Enzyme purification and assay 4. Results 4.1 Substrate potential of aminoalkylaziridines 4.2 Competitive nature of inhibition 4.3 Irreversibility of inhibition 5. Discussion 6.. Acknowledgement 7. References

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…After compensating for the added fumarate salt, this concentration corresponds to 0.0137mM BAPN, as compared with the 0.137mM BAPN concentration used in the current study. Given that this tenfold higher 0.137mM BAPN concentration corresponded to five times the half-maximal inhibitory BAPN concentration in vivo [49,50], we expected greater lysyl oxidase inhibition to be induced in vitro . In other words, the quantitative analysis of collagen synthesized in vitro reflects a direct rather than systemic effect of lysyl oxidase inhibition by BAPN.…”
Section: Discussionmentioning
confidence: 99%
“…After compensating for the added fumarate salt, this concentration corresponds to 0.0137mM BAPN, as compared with the 0.137mM BAPN concentration used in the current study. Given that this tenfold higher 0.137mM BAPN concentration corresponded to five times the half-maximal inhibitory BAPN concentration in vivo [49,50], we expected greater lysyl oxidase inhibition to be induced in vitro . In other words, the quantitative analysis of collagen synthesized in vitro reflects a direct rather than systemic effect of lysyl oxidase inhibition by BAPN.…”
Section: Discussionmentioning
confidence: 99%
“…While the bulk quantification of crosslinks using high performance liquid chromatography would be inconclusive in the current study due to the modest effect of BAPN and the relative amount of pre-existing tissue to tissue formed during BAPN treatment, quantifying crosslinks in a model where a higher dose was used over a longer period is needed to conclude whether or not the modest effect in this model is due to a failure to adequately inhibit crosslinks or simply enzymatic crosslinks are not as important in determining macroscale mechanical properties as believed. Additionally, the timing of the injections in future studies should be optimized to coincide with the circadian rhythm of bone formation so that over the approximately 2.5 hours when the serum concentration of BAPN is above the half maximal inhibitory concentration of 25 μM bone formation is at its peak [ 42 45 ]. Alternatively, other administration routes that do not rely on timing a bolus of BAPN may be more successful in generating an overt mechanical disease state such as osmotic pumps [ 46 ] or dietary supplements [ 47 , 48 ] that deliver near constant or repeated doses over the course of the day to maintain efficacy despite rapid clearance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that treatment with BAPN decreases collagen cross-linking and myocardial stiffness in the left ventricle of normal adult pigs (32). Vicinal diamines (a certain kind of halogenated allyl amines), hydralazines, and aminoalkylaziridines with strict structural requirements are also inhibitors of LOX (17,47,48). Taurine, niacine, heparin, and 2-mercaptopyridine-N-oxide have been also reported as LOX inhibitors in vitro (1,19) and in vivo (3).…”
Section: Therapeutic Modulation Of Lox In Cardiac Diseasesmentioning
confidence: 99%